Pathophysiology and Cardiac Autopsy in COVID-19 related Myocarditis - Gatta, Francesca; Dolan, Ciaran (Cardiology and Cardiovascular Medicine, 2020)
On the 11th of March 2020, the coronavirus disease-2019 (COVID-19) was declared a global Pandemic by the World Health Organization. This infectious disease is caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS?CoV?2) which emerged in Wuhan, China, in December 2019, and rapidly spread across the world. Respiratory involvement ranging from a mild flu-like illness to potentially lethal acute respiratory distress syndrome is the predominant clinical manifestation. However, major cardiovascular complications have also been reported, with myocarditis contributing to mortality in up to a third of cases with severe COVID-19. In the presence of normal coronary arteries, acute myocarditis in SARS-CoV-2 cases may present with varying clinical severity, including myopericarditis, fulminant myocarditis, and cardiogenic shock. The pathophysiology of myocardial injury caused by SARS-CoV2 is not fully understood. The extent to which direct viral cytopathic effects contribute to the pathophysiology, compared with indirect systemic toxicity, remains unclear. The autopsy-proven myocardial localisation of the virus has rarely been reported.